EULAR definition of difficult-to-treat rheumatoid arthritis. Issue 1 (1st October 2020) - Nagy, György; Roodenrijs, Nadia MT; Welsing, Paco MJ; Kedves, Melinda; Hamar, Attila; van der Goes, Marlies C; Kent, Alison; Bakkers, Margot; Blaas, Etienne; Senolt, Ladislav; Szekanecz, Zoltan; Choy, Ernest; et al.
Abstract : Background: Despite treatment according to the current management recommendations, a significant proportion of patients with rheumatoid arthritis (RA) remain symptomatic. These patients can be considered to have 'difficult-to-treat RA'. However, uniform terminology and an appropriate definition are lacking. Objective: The Task Force in charge of the " Development of EULAR recommendations for the comprehensive management of difficult-to-treat rheumatoid arthritis" aims to create recommendations for this underserved patient group. Herein, we present the definition of difficult-to-treat RA, as the first step. Methods: The Steering Committee drafted a definition with suggested terminology based on an international survey among rheumatologists. This was discussed and amended by the Task Force, including rheumatologists, nurses, health professionals and patients, at a face-to-face meeting until sufficient agreement was reached (assessed through voting). Results: The following three criteria were agreed by all Task Force members as mandatory elements of the definition of difficult-to-treat RA: (1) Treatment according to European League Against Rheumatism (EULAR) recommendation and failure of ≥2 biological disease-modifying antirheumatic drugs (DMARDs)/targeted synthetic DMARDs (with different mechanisms of action) after failing conventional synthetic DMARD therapy (unless contraindicated); (2) presence of at least one of the following: at least moderate disease activity; signs and/or symptoms suggestive of active disease; inability to taper glucocorticoid treatment; rapid radiographic progression; RA symptoms that are causing a reduction in quality of life; and (3) the management of signs and/or symptoms is perceived as problematic by the rheumatologist and/or the patient. Conclusions: The proposed EULAR definition for difficult-to-treat RA can be used in clinical practice, clinical trials and can form a basis for future research.